On the Essence of Religious Extremism - Andrey V. Sigarev (Сибирское юридическое обозрение)
The article discusses the concept and features of religious extremism, problems of law enforcement in this area. Analysis of judicial practice leads to the conclusion about the limited effectiveness of legal remediesin qualifying and countering extremism. Improving the system of prohibitions and sanctions should be done in parallel with the development of other means of inter-religious cooperation.